Lower cervical C6/C7 andersson lesion with upper cervical C1/C2 fracture in ankylosing spondylitis: a case report and literature review - Qiao, Han; Cheng, Xiaofei; Tian, Haijun; Zhao, Changqing; Sun, Xiaojiang; Zhao, Jie (Frontiers in Surgery, 2025)
Cervical andersson lesions (ALs) are rare in patients with ankylosing spondylitis (AS), and even more rare in patients with simultaneous superior cervical atlantoaxial fracture and dislocation. Here, we present a case of C1 Jefferson fracture (C1 bilateral posterior arch fracture), C2 odontoid, lateral mass, vertebral fracture (nonclassic C2 hangman fracture), traumatic posterior atlantoaxial dislocation (AAD) and C6/C7 AL in a long-standing AS cervical spine. The patient with traumatic AS-related cervical fractures underwent a two-stage surgery. The stage I surgery involved a posterior atlantoaxial reduction and fixation surgery combined with C5/C6/T1/T2 posterior pedicle screw fixation plus C6/C7 decompression. One week later, C6/C7 anterior cervical corpectomy decompression and fusion (ACCF) with long anterior plate stabilization combined with iliac crest bone graft transplantation was performed for stage II surgery. The patient recovery observed during follow-up was satisfactory. Nine-month postoperative radiological images revealed fracture union of the upper and lower cervical spine with optimal reduction of the atlantoaxial segment. In conclusion, lower cervical ALs with simultaneous upper cervical C1/C2 fractures in the AS are very rare. Posterior C1-C2 fixation combined with C6-C7 AL corpectomy/fusion and posterior pedicle screw fixation may offer a desirable alternative approach for this complex case of cervical trauma. During treatment, complete decompression, effective reduction, and potent stabilization can comprehensively improve the clinical prognosis.